The importance of immediate physical therapy in the postoperative period of the anterior cruciate ligament (Research, Society and Development, 2022)
Physiotherapeutic treatment works in the post-operative rehabilitation of the reconstruction of the anterior cruciate ligament (ACL), with the function of recovering mobility in the knee joint, reducing edema and pain. There are several resources and treatments used in physical therapy that can contribute to a faster recovery of the patient. This study aims to expose and analyze the importance of immediate physiotherapy in the postoperative period of the ACL, in order to compare the treatment methods used in the immediate postoperative rehabilitation of ACL, as well as the knowledge in the scientific scope of specialized physiotherapy care in 48 hours, aiming at well-being, quality of life and prevention. The methodology applied in this research follows the recommendations of integrative reviews, the selection of articles was defined as inclusion criteria: articles published in the last five years and field research articles. The search excluded articles from literature reviews, articles that did not address the proposed theme, and research comparing interprofessional techniques. In common consensus, they show that the recovery of the patient after ACL reconstruction is not only faster, but also more effective, with more favorable prognoses, and prevents immobility syndrome, irreversible lesions and calcifications. Thus, it is concluded that immediate and fundamental physiotherapy is effective in post-operative ACL surgery.